Religious identity as a determinant of confrontation of Russian national-radical circles of Islam = Tożsamość religijna jako wyznacznik konfrontacji rosyjskich środowisk narodowo-radykalnych z islamem - Michalak. Ryszard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this article is to show as an indicator of religious communities confront Russian national-radical Islamic environments. Author recounts the relationship between these entities in view of the last decade and make estimate for Russia: the world conflict Russian-Orthodox and Islamic will be increasing, and another consequence of this situ-ation may be changing the balance of power in the party - as far as Western Europe, however, respect the democratic nationalist formations way to power, then in Russia can be decisive (in accordance with the Russian specifics "street protest party" and ethos of revolutionary in that country) sample decomposition of the political system through revolutionary.
Keywords: radykalny nacjonalizm; determinanty religijne; prawosławie; islam; sprzężenie zwrotne; radical nationalism; determinants of religious; Orthodoxy; feedback